Decreased fat accumulation in 3T3‐L1 pre‐adipocytes treated with extracts of heat‐processed soy flour and breads. (10th October 2013) - Shin, Doo‐Jee; Choi, Induck; Yokoyama, Wallace H.; Kim, Mi‐Ja; Kim, Yookyung
Summary The potential anti‐adipogenic effects of gluten‐free soy breads made from germinated soybean (GS), steamed soybean (SS) or roasted soybean (RS) were evaluated in an in vitro adipocyte cell model. GS and RS increased the total phenolic (TP) and total flavonoid (TF) contents of flours compared with the raw soybean (NS) flour. RS and GS had the highest TP (1.04 GAE mg g−1) and TF (0.92 CAE mg g−1) contents. Baking increased the TP content of breads, 0.09–0.26 GAE mg g−1, compared with the flours. Fermentation during breadmaking increased the DPPH scavenging activities compared with the flours. The ABTS scavenging exhibited similar patterns to those of DPPH. Lipid accumulation in 3T3‐L1 cells shows that the alcoholic extracts (100 μg mL−1) of SS flour and bread decreased adipocyte differentiation by 1.6‐ and 2.1‐fold, respectively, compared with control. SS bread extract substantially downregulated the adipogenesis‐related genes such as acetyl‐CoA carboxylase and glycerol‐3‐phosphate dehydrogenase.